PENGARUH AUDIT REPORT LAG DAN KUALITAS AUDIT TERHADAP AUDITOR SWITCHING (STUDI EMPIRIS PADA PERUSAHAAN YANG TERCATAT DI INDEKS KOMPAS 100 BURSA EFEK INDONESIA TAHUN 2020-2022) - Sagala, Clarissa Grace S.; Malau, Harman (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
ABSTRACT This study examines the impact of audit report lag and audit quality on auditor switching among companies listed in the Kompas 100 Index of the Indonesia Stock Exchange for the years 2020-2022. Utilizing a quantitative approach and secondary data sources, this research successfully collected samples from 51 companies, representing a total of 153 data samples, through purposive sampling from the entire 100 companies. The analysis was conducted using descriptive statistical techniques and logistic regression, with data processing through SPSS version 29. According to the results, the Nagelkerke R Square value of 0.061 indicates that audit report lag and audit quality can only explain 6.1% of the influence on auditor switching, while 93.9% is influenced by other variables outside of this study. The findings shows that neither audit report lag nor audit quality has a significant effect on auditor switching, both partially and simultaneously. Keywords: Audit Report Lag, Audit Quality, Auditor Switching